Pengaruh Perbedaan Waktu Setting pada Alat Pancing Ulur (Hand line) terhadap Hasil Tangkapan Ikan Kakap Merah (Lutjanus sp) di Perairan Brondong Kabupaten Lamongan - Muhammad Galih Wijianto; M Tajuddin Noor; Exist Saraswati (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
Red snapper (Lutjanus sp) in Brondong waters, Lamongan Regency, is one of the main sources of livelihood for local fishermen. To increase the catch, optimizing the use of fishing gear, including setting time, is important. This study aims to determine the effect of differences in setting time on hand line fishing gear on red snapper catches. The study was conducted using the experimental fishing method, by dividing the setting time of hand line fishing gear into 2 treatments, namely morning 08.00-11.00 and afternoon 15.00-18.00. Based on the T test on paired samples, the average catch at 08.00-11.00 WIB was 2,131 with a total of 34.1 kg, while at 15.00-18.00 WIB, the average catch reached 6.4 with a total of 102.4 kg. The T-test results show that the t-count is greater than the t-table, so the null hypothesis is rejected and it can be concluded that there is a significant difference between the red snapper catches in the two time periods. Red snapper tends to be more active in foraging in the afternoon to evening, in line with its nocturnal nature. Several studies have stated that predatory fish such as red snapper hunt more when the light begins to dim. However, other factors such as food availability and physical conditions of the waters can also affect fish feeding activity. These findings provide additional insight into the feeding behavior of red snapper and the factors that influence its presence in the waters.